Counselors' Claims of Insufficient Knowledge in Academic Writing Consultations. Issue 6 (19th September 2021) - Skogmyr Marian, Klara; Henricson, Sofie; Nelson, Marie
ABSTRACT: Contributing to academic literacies research, this study investigates how counselors at university writing centers in Sweden and Finland handle the micro-level management of knowledge in advice-giving. While writing counselors are experienced in academic writing, they are not necessarily familiar with students' subject areas and may also lack access to other relevant information, such as specific writing instructions. Using Conversation Analysis, we examine how writing counselors address their lack of relevant knowledge through claims of insufficient knowledge (CIK). CIKs are typically used in assessment activities, to downgrade both positive and negative assessments, but sometimes also to upgrade positive assessments. Our findings demonstrate how the distribution of knowledge is negotiated in academic writing consultations and illustrate the epistemic complexity of this setting.